Worlding cities Asian experiments and the art of being global - Roy, Ananya; Ong, Aihwa (Chichester, West Sussex John Wiley & Son, 2011)
"Worlding Cities is the first serious examination of Asian urbanism to highlight the connections between different Asian models and practices of urbanization. It includes important contributions from a respected group of scholars across a range of generations, disciplines, and sites of study.. Describes the new theoretical framework of 'worlding'. Substantially expands and updates the themes of capital and culture. Includes a unique collection of authors across generations, disciplines, and sites of study. Demonstrates how references to Asian power, success, and hegemony make possible urban development and limit urban politics".
"From Dubai to Delhi and from Singapore to Shanghai, cities across Asia are sites of intense experiments with different ways of being global. This book intervenes in urban theory focused on established global cities, and instead argues that the urban globality is something that is continually being imagined, assembled, and contested. Greater Asia is a region of vibrant innovations in urban design, built forms, governance, aesthetics, and politics. Worlding Cities draws attention to diverse projects of 'worlding' and "reworlding" that draw upon local and transnational relationships. Alternative ways of being global are instantiated through practices of mobility, modeling, and speculation that inter-reference other Asian sites. As many of the essays in this book illustrate, different Asian futures are being shaped in cities, from green governmentality to eco-city, from corporate speculations to political contestations over urban development, from "world-class" city branding to demands for "world-class" services, and from sky-high hopes to dashed dreams on the ground for city-dwellers and migrants. This inter-generation and interdisciplinary group of authors offers the first serious examination of diverse actors, energies, and conditions at play in defining new worlds of inter-Asian urbanism".
Singapore as model: planning innovations, knowledge experts / Chua Beng Huat -- Urban modeling and contemporary technologies of city-building in China: the production of regimes of green urbanisms / Lisa Hoffman -- Planning privatopolis: representation and contestation in the development of urban Integrated mega-projects / Gavin Shatkin -- Ecological urbanization: calculating value in an age of global climate change / Shannon May -- Retuning a provincialized middle class in Asia's urban postmodern: the case of Hong Kong / Helen F. Siu -- Cracks in the faðcade: landscapes of hope and desire in Dubai / Chad Haines -- Asia in the mix: urban form and global mobilities : Hong Kong, Vancouver, Dubai / Glen Lowry and Eugene McCann -- Hyperbuilding: spectacle, speculation, and the hyperspace of sovereignty / Aihwa Ong -- Speculating on the next world city / Michael Goldman -- The blockade of the world-class city: dialectical images of Indian urbanism / Ananya Roy -- Rule by aesthetics: world-class city making in Delhi / D. Asher Ghertner -- Conclusion: postcolonial urbanism: speed, hysteria, mass dreams / Ananya Roy.
Includes bibliographical references and index.
Keywords: Urbanization -- Asia; Globalization -- Asia